Characteristics of Red Bean-Mocaf biscuits as alternative high-fiber low-sugar snacks - Afifah, Diana Nur; Ayustaningwarno, Fitriyono; Febriyanti, Farah; Nadia, Iluni Prista; Ratri, Liesty Kurnia; Rahadiyanti , Ayu; Purwanti , Rachma; Wijayanti , Hartanti Sandi; Nuryanto,; Ardiaria, Martha; Murwani , Retno; Zhu, Fan; et al. (Progress in Nutrition, 2024)
Background and aim: Biscuits are very popular in Indonesia, but the most common types in the market have low nutritional content. Meanwhile, red bean flour and Mocaf are rich in nutrients, especially fiber, and their combination is expected to form a biscuit product that is nutritious and highly liked. Therefore, this study aims to analyze the nutritional value, organoleptic quality, resistant starch and digestibility starch, as well as the shelf life of red bean and mocaf biscuit.Methods: A total of four formulation of red bean flour to Mocaf ratio were compared, 44%:0% (F1), 31%:13% (F2), 22%:22% (F3), and 13%:31%.Results: F2 was the best formulation which had protein (12.38%), dietary fiber (14.95%), and total sugar contents (4.09%) appropriate to the quality requirements of biscuits according to SNI. It also had high fiber and low sugar which is in line with the National Agency of Drug and Food Control, while the shelf life was 31 days at a temperature of 25 o C.ConclusionsThe addition of Mocaf in the biscuits increased starch digesbility and resistant starch, thus formula without Mocaf had the highest resistant starch (2.07%) and the lowest starch digestibility (43.61%).